2019
DOI: 10.20448/2001.51.33.46
|View full text |Cite
|
Sign up to set email alerts
|

Does Corruption really affect the Growth of Entrepreneurship in Zimbabwe?

Abstract: Like in most developing countries, the level of entrepreneurship growth as measured by the number of new firm start-ups has become a central economic issue in Zimbabwe. Necessity and opportunity-driven entrepreneurial activities in the country are being driven by weakening economic growth, poverty, idiosyncratic macro-uncertainties and high levels of unemployment. The country has consistently been listed by the Transparent International Perception of Corruption Index as one of the most corrupt countries in Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…More corruption is likely as a result of investors attempting to overcome the effects of political instability on future profitability and expected long-term returns. These results agree with the two studies by Muzurura (2017Muzurura ( , 2019 that found political instability led to excessive investments in unproductive activities, such as lobbying politicians and bureaucrats, manipulating the political system, and payments to corrupt officials. A recent upsurge of political instability in the Zimbabwe could be a consequence of corruption and its attendant issues, such as further income inequality and poverty: as corruption increases corruption, the beneficiaries grow wealthier, posing a greater incentive to groups lower down the economic hierarchy to engage in similar, illegal, or violent activities.…”
Section: Political Instability and Corruptionsupporting
confidence: 92%
See 2 more Smart Citations
“…More corruption is likely as a result of investors attempting to overcome the effects of political instability on future profitability and expected long-term returns. These results agree with the two studies by Muzurura (2017Muzurura ( , 2019 that found political instability led to excessive investments in unproductive activities, such as lobbying politicians and bureaucrats, manipulating the political system, and payments to corrupt officials. A recent upsurge of political instability in the Zimbabwe could be a consequence of corruption and its attendant issues, such as further income inequality and poverty: as corruption increases corruption, the beneficiaries grow wealthier, posing a greater incentive to groups lower down the economic hierarchy to engage in similar, illegal, or violent activities.…”
Section: Political Instability and Corruptionsupporting
confidence: 92%
“…Such an effect is likely to be far more damaging, especially in the case of Zimbabwe, as foreign investment can often bestow immense benefits on developing economies: introducing cutting-edge production technologies, enhancing the development of human capital and management techniques, as well as expediting the rate of technical progress and output growth in the recipient country. These findings agree with those of , Dutta and Sobel (2016), Muzurura (2019), Olken and Pande (2012), and O'Toole and Tarp ( 2014), all who demonstrated that corruption harms both domestic and foreign investment by redirecting resources toward economic activities and sectors that offer less stimulation to the wider economy. Nevertheless, this study differs from those that reported corruption may be a major cause of FDI in resource-rich but poor countries (see Pinto and Zhu, 2016).…”
Section: Foreign Direct Investment (Fdi) and Corruptionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although commendable efforts have been made by the government in this regard, cumbersome bureaucracy, stringent regulations and corruption rentals have slowed down the pace of entrepreneurship growth in Zimbabwe. Muzurura (2019) states that corruption is amongst the impediments to entrepreneurship in Zimbabwe, which tends to have a sanding instead of greasing 'effect on the wheels of entrepreneurship growth'.…”
Section: Informal Sector and Entrepreneurship In Zimbabwementioning
confidence: 99%
“…Other studies have also arrived at similar conclusions. For Zimbabwe, the empirical analysis of Muzurura (2017) showed that high levels of corruption/rent-seeking are detrimental to economic growth. For Nigeria, the empirical analysis reveals that the relationship between the level of corruption and economic growth is a long-run one, and that corruption’s impact on economic growth in the country is negative (Nwankwo, 2014).…”
Section: The Corruption and Sustainable Development Relationship In A...mentioning
confidence: 99%